1987
DOI: 10.1111/j.1095-8649.1987.tb05272.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between maternal size, egg diameter, time of spawning season, temperature, and length at hatch of Atlantic silverside, Menidia menidia

Abstract: Eggs were stripped from gravid Atlantic silversides collected on two occasions. once during the early part and once during the late part of the natural spawning season. Unfertilized egg diameter was not correlated with length of the female. nor was it significantly larger during the early part of the season. Eggs were fertilized and incubated in the laboratory. Larval length at hatch was measured every 24 h during the hatching period after embryos were incubated at I8 or 25" C. Lower incubation temperature cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 17 publications
2
23
1
Order By: Relevance
“…Maternal factors have, no doubt, a major influence on early life history traits via spawning site selection, fecundity, egg quality, egg size, and provisioning of yolk (Bengtson et al, 1987;Green, 2008). Females contribute in contrast to males, not only 50% of the nuclear genomic DNA, but also non genetic components for instance in form of a yolk and carotenoid supply (Rideout et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal factors have, no doubt, a major influence on early life history traits via spawning site selection, fecundity, egg quality, egg size, and provisioning of yolk (Bengtson et al, 1987;Green, 2008). Females contribute in contrast to males, not only 50% of the nuclear genomic DNA, but also non genetic components for instance in form of a yolk and carotenoid supply (Rideout et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Females contribute in contrast to males, not only 50% of the nuclear genomic DNA, but also non genetic components for instance in form of a yolk and carotenoid supply (Rideout et al, 2004). Maternal factors influence initial offspring quality and size primarily by influencing egg quality and size (Bengtson et al, 1987;Chambers and Leggett, 1996;Marteinsdottir and Steinarsson, 1998). Generally, larger and older females normally produce relatively large offspring, which according to the ''bigger is better hypothesis" may confer advantages to offspring during ELH (Chambers and Leggett, 1996;Trippel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Fertilized eggs can be created using concentrated sperm dilutions (e.g., dry fertilization) which potentially increases the number of fertilized eggs per sample. Geffen, 1992;Rideout et al, in press), as maternal effects are generally presumed to control this early life stage (Bengtson et al, 1987;Chambers et al, 1988;Chambers and Leggett, 1996). The male effect can be studied for several weeks or months as larvae continue to grow and commence exogenous feeding and become juveniles.…”
Section: Paternal Effects On Hatching Success Larval Traits and Earlmentioning
confidence: 99%
“…Quantity of spawned eggs has been positively correlated with maternal length, age and nutritional condition (Bagenal, 1973;Kjesbu et al, 1991Kjesbu et al, , 1996. Variability in size and quality of eggs influences early life success and presumably recruitment (Blaxter and Hempel, 1963;Bengtson et al, 1987;Chambers, 1997;Pepin et al, 1997;. What then is the male's role in determining recruitment success?…”
Section: Introductionmentioning
confidence: 99%
“…Significant maternal effects in larval traits have been observed in a few species. The traits for which these effects have been documented are size at hatch (chum salmon (Oncorhynchus keta), Beacham and Murray 1985; Atlantic silverside (Menidia menidia), Bengston et al 1987), yolk volume at hatch (chum salmon, Beacham and Murray 1985;capelin (Mallotus villosus), Chambers et al 1989), and size at metamorphosis (winter flounder (Plueronectes americanus), Chambers and Leggett 1992). Chambers and Leggett (1996) concluded that "body size during larval life was likely to be significantly influenced by maternal effects."…”
Section: Introductionmentioning
confidence: 99%